The physical work environment's impact on wellbeing : the moderating role of time spent in building. - Maluleke, Musa (My University, 2013)
This study was concerned with investigating the perceptions of the conditions of the physical work environment on the psychological and physical wellbeing of employees at Nedbank. This was an important study to carry out due to the fact that people are increasingly spending time indoors more especially in the offices in which they work. Thus it becomes important to investigate the effects that the physical work environment in which people work has on their psychological and physical wellbeing. The buildings investigated in this study were green buildings, as they were concerned with limiting the negative impact of the physical work environment on the wellbeing of employees and the environment. The sample utilised in this study consisted of three hundred and forty nine (n=349) participants of Nedbank from two recently refurbished buildings known as Phase II and Ridgeside, the sampling technique utilised in order to obtain this sample was purposive sampling. The statistical analysis which were utilised was the multiple regression analysis which was used in order to find out which building conditions influenced psychological and physical wellbeing, whilst a partial correlation analyses was performed to investigate the moderating effect of time spent in building. From these analyses it was found that perceptions of the conditions of the physical work environment had a greater influence on the physical wellbeing of employees. Perceptions of the conditions of the physical work environment were found to have a lesser influence on the psychological wellbeing of employees at Nedbank. Results also revealed that time spent in building was not a moderator of the relationships between the perceptions of the conditions of the physical work environment with psychological and physical wellbeing respectively.
Keywords: Employees--Job stress--South Africa.; Work environment--Psychological aspects.; Bank employees--Health and hygiene--South Africa.